Pengaruh Pengetahuan Tentang Bank Syariah, Religiusitas, Lingkungan Sosial, Dan Uang Saku Terhadap Minat Menabung Mahasiswa Di Bank Syariah (Studi Kasus pada Mahasiswa STIE Bank BPD Jateng) - Riza Mega Iryani; Rudi Suryo Kristanto (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of knowledge about islamic banking, religiosity, social environtment, and pocket money on student in saving at islamic banks. The data used in this study is primary data based on a sample of 133 respondent of STIE Bank BPD Central Java taken by purposive sampling and snowball sampling. The data was processed using the Statistical Product Service Solutions (SPSS) analysis tool. By using multiple linear regression anaysis shows that knowledge of islamic banks, religiosity, social environment, and pocket money can explain the variable interest in saving by 79,1 percent. With the result of the analysis which shows that the variables of knowledge about islamic banks, religiosity, and social environtment have a significance of respectively 0,000 < 0,05; 0,012 < 0,05’ and 0,000 < 0,05, which means that the variables of knowledge about islamic banks, religiosity, and social environtment have a significant influence on student’s saving interest in islamic banks. While the pocket money variable has a significance of 0,208 > 0,05, which means that pocket money has no effect on interest in saving in islamic banks.